Latin America in a new world - Lowenthal, Abraham F. ed. (Westview P. BoulderUS, 1994)
Presents broad overviews on inter-American relations after the Cold War. Focuses on Latin America's relations with major extra-hemispheric regions, and on the policy responses by the nations of the Western Hemisphere to the challenges posed by the new world.